Improvement of Control Efficacy of Mancozeb Wettable Powder against Citrus Melanose by Mixing with Paraffin Oil - Pyoung-Ho Yi; Jae-Wook Hyun; Rok-Yeon Hwang; Kwang-Sik Kim (Research in Plant Disease, 2014)
This study was carried out to determine the effect of mixing with paraffin oil on rainfastness of mancozeb on citrus fruits and assay the improvement of control effect of mancozeb against citrus melanose by mixing with paraffin oil. In artificial rainfall condition (7.2 mm/hr), the attached contents of mancozeb on detached fruits were the most in treatment of mancozeb 0.2% + paraffin oil 0.1% as the contents was 7.43 μg/cm2 after treatment of rainfall for 10 hr. In open field condition, the contents of attached mancozeb on fruits were significantly more in treatment of mancozeb 0.2% + paraffin oil 0.1% or 0.25% than the other treatments 1, 15 and 25 days after treatment 2009 and 2010 seasons. The disease incidence was significantly lower in treatment of mancozeb 0.2% + paraffin oil 0.1% or 0.25% than treatment of mancozeb 0.2% only 2009, 2010 and 2011 seasons. Based on this study, it was suggested that the control effect of mancozeb against citrus melanose can be improved by mixing with paraffin oil.